'Exiled from the Musical Activities of His Homeland': Dean Dixon in the Australian and African American Press During the Era of Immigration Reform. Issue 1 (3rd July 2021) - Coady, Christopher
Abstract: During the 1960s, international and domestic pressure on the Australian government led to a softening of restrictive immigration practices that had played a key role scaffolding what is commonly referred to as the White Australia policy. The appointment of Dean Dixon—an African American expatriate—to lead the Sydney Symphony Orchestra in 1963 was celebrated by both the government and a cohort of journalists in the Australian press as an important milestone in the immigration reform effort. In this article, I discuss the paradox of how Dixon's appointment allowed notions of a racially progressive society to circulate in the Australian press in ways that simultaneously entrenched what Gwenda Tavan refers to as the 'indices' of 'whiteness' and 'Britishness' anchoring assimilationist thought. I then outline how the African American press, in contrast, framed Dixon's work abroad as a challenge to ideologies of white supremacy. Threading these two stories of Dixon's migration together reveals different views on the possibilities bound up in his appointment and a fundamental tension between the Australian and African American press's understanding of the kind of cultural work Dixon undertook while leading the Sydney Symphony Orchestra.